1B.10: DOES THE RIGHT ARM KNOW WHAT THE LEFT ARM IS DOING? ETHNIC VARIATIONS IN CLINICAL INTERARM DIFFERENCE AND RELATIONSHIP TO WHITE COAT EFFECTS. (June 2015) - Schwartz, C.; Koshiaris, C.; Clark, C.; Haque, M. Sayeed; Gill, P.; Mant, J.; Martin, U.; McManus, R.
Abstract : Objective: Evidence suggests an interarm difference (IAD) of >=10mmHg in blood pressure (BP) is associated with a greater incidence of cardiovascular disease. Effect of ethnicity on the prevalence of this difference has not been reported. Design and method: The Blood Pressure in Ethnic Groups Study (BP-Eth), based in primary care, investigated the relationship between ethnicity and different methods of BP measurement. Using these data the prevalence of a significant IAD was investigated in 770 people (300 White British, 229 South Asian, 241 African-Caribbean). Repeated BP measurements were obtained simultaneously in the right and left arm using two BP-Tru machines and comparisons made between the first reading, mean of 2nd/3rd readings and mean of 2nd-6th readings for patients with and without known hypertension. Results: No significant difference was seen in the prevalence of a systolic IAD between ethnicities whichever combinations of BP measurement were used and whether or not an individual was hypertensive. Overall the prevalence of IAD fell as more measurements were used in the comparison: first measurement (n = 161, 22%), mean 2nd/3rd (113, 16%) and mean 2–6th (78, 11%) (first vs clinic and research mean p < 0.001). To investigate whether this change in IAD prevalence with repeated measurement was due to a white coat effect (WCE), the three types of measurement were compared with participants' mean daytime ambulatory readings (ABPM). WCE was defined as Clinic BP >=10mmHg higher than ABPM. Unadjusted results show patients with a WCE were twice as likely to have an IAD on their first BP measurement (OR 2.1, 95% CI 1.4 - 3.1), mean 2nd/3rd (2.1, 95% CI 1.3 - 3.4) and mean 2–6th (2.1, 95% CI 1.2 - 3.9) compared to those without a WCE. Conclusions: Ethnicity did not affect the prevalence of IAD in people with or without hypertension. However the prevalence of IAD was affected by the number of readings suggesting an element of white coat effect and this was confirmed by comparison with ambulatory monitoring. Therefore ABPM may play an important role in the investigation of those with >=10mmHg interarm blood pressure difference.